Partnering with Student Ambassadors to Create More Inclusive Universities : Best Practices for Collaboration - Ruxandra Foloștină; Clare Gartland; Albina Khasanzyanova; Ümit Çelen (Routledge, 2025)
Designed to promote the social and educational inclusion of disadvantaged groups and nontraditional learners, this book provides all the information needed to train networks of student ambassadors to improve student diversity and inclusion in higher education.Recognising that student ambassadors can play a significant role in addressing inequalities by supporting younger students in developing social and cultural capital, the book uses evidence-based information and best practices for training student ambassadors to enable them to promote social inclusion and educational progression. Packed full of activities covering the topics of STEM, the Arts, the Social Sciences, Humanities, and Health, each activity is presented in line with the United Nations Sustainable Development Goals and can be used in the training of student ambassadors themselves, or in schools with students aged 11–14 to empower them to become active, engaged, and involved in their local communities. By participating in these activities, student ambassadors will be able to effectively engage with more students from disadvantaged or marginalised communities, and students from these communities will be better equipped to navigate progression routes into higher education.This is a must-read book for all those interested in the theory and practicalities of making their universities more inclusive with the help of student ambassadors. It is a hands-on resource that will be particularly useful for those higher education institutions that are interested in implementing student ambassadors, as well as anyone interested in promoting social justice and challenging traditional patterns of progression to higher education.